Comportamento de cultivares de girassol em função da época de semeadura na regiao de Ponta Grossa, PR - Thomaz, Giovani Luiz (2008)
The search of crops for biodiesel production in Brazil is increasing. The sunflower (Helianthus annuus L.) has high oil content, has low demand of water and has the possibility of being cultivated in different times of the year. These characteristics may turn out this crop to be important for biodiesel production, occupying “spaces” in production systems and crop rotations adopted by farmers. Accordingly, one study was carried out, at the Experimental Station of Ponta Grossa of Instituto Agronômico do Paraná – IAPAR, with the objective of evaluating the effect of sowing date on the cycle, agronomic characteristics, yield of achenes, oil content and oil yield. Four cultivars of sunflower (Aguará 4, Catissol, Hélio 250 e M734) were tested in ten sowing dates, spaced around twenty days, with the first sowing day in July 30, 2007 and the last in January 28, 2008. The highest yield of achenes and oil occurred on crops at the end of July, in August and in September. The cultivars M734 e Aguará 4 had the highest yield of achenes. The sowing dates influenced all the variables studied.